State of the evidence: mechanical ventilation with PEEP in patients with cardiogenic shock. Issue 24 (28th March 2013) - Wiesen, Jonathan; Ornstein, Moshe; Tonelli, Adriano R; Menon, Venu; Ashton, Rendell W
Abstract : The need to provide invasive mechanical ventilatory support to patients with myocardial infarction and acute left heart failure is common. Despite the large number of patients requiring mechanical ventilation in this setting, there are remarkably few data addressing the ideal mode of respiratory support in such patients. Although there is near universal acceptance regarding the use of non-invasive positive pressure ventilation in patients with acute pulmonary oedema, there is more concern with invasive positive pressure ventilation owing to its more significant haemodynamic impact. Positive end-expiratory pressure (PEEP) is almost universally applied in mechanically ventilated patients due to benefits in gas exchange, recruitment of alveolar units, counterbalance of hydrostatic forces leading to pulmonary oedema and maintenance of airway patency. The limited available clinical data suggest that a moderate level of PEEP is safe to use in severe left ventricular (LV) dysfunction and cardiogenic shock, and may provide haemodynamic benefits as well in LV failure which exhibits afterload-sensitive physiology.